1996
DOI: 10.1007/s004410050635
|View full text |Cite
|
Sign up to set email alerts
|

Light-microscopic immunolocalization of fibroblast growth factor-1 and -2 in adult rat kidney

Abstract: The fibroblast growth factors (FGFs) are a family of conserved polypeptides known to regulate cell differentiation and proliferation. We have used avidin-biotin-enhanced indirect immunohistochemistry to localize FGF-1 and FGF-2 in the rat kidney. The most consistent specific immunostaining pattern is found in paraffin sections from kidneys perfusion-fixed with 4% paraformaldehyde in 0.1 M phosphate buffer. Intracellular immunoreactivity for FGF-1 and FGF-2 is co-localized in visceral (podocytes) and parietal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In adult human kidney, FGF-2 expression has been described in glomerular endothelial, parietal, and visceral cells, tubular epithelial cells, and interstitial fibroblasts (5,11,37). Our data demonstrated an upregulated expression of FGF-2 in DN in vivo.…”
Section: Discussionsupporting
confidence: 61%
“…In adult human kidney, FGF-2 expression has been described in glomerular endothelial, parietal, and visceral cells, tubular epithelial cells, and interstitial fibroblasts (5,11,37). Our data demonstrated an upregulated expression of FGF-2 in DN in vivo.…”
Section: Discussionsupporting
confidence: 61%
“…27,30 Therefore, we sought to detect intraglomerular gene expression of FGF2. However, our glomerular analysis using in situ hybridization of FGF2 and immortalized cell lines showed virtually undetectable increased expression in the diabetic kidney.…”
Section: Glypican-5 In Diabetic Nephropathymentioning
confidence: 99%
“…the complete loss of Fgf9 function during kidney development results in a failure of nephron formation prior to the S-shaped body stage. Cauchi et al (1996) reported that FGF-1 and FGF-9 proteins are localized in glomeruli, proximal tubules, distal tubules, and collecting ducts of adult rat kidneys. In adult rat kidneys, FGF9 has been localized in medullary interstitial cells (Ichimura et al, 1996).…”
Section: Discussionmentioning
confidence: 99%